BlockPy: An Open Access Data-Science Environment for Introductory Programmers. - Bart, Austin Cory; Tibau, Javier; Tilevich, Eli; Shaffer, Clifford A.; Kafura, Dennis (Computer (00189162), 2017)
Non-computer science majors often struggle to find relevance in traditional computing curricula that tend to emphasize abstract concepts, focus on nonpractical entertainment, or rely on decontextualized settings. BlockPy, a web-based, open access Python programming environment, supports introductory programmers in a data-science context through a dual block/text programming view. The web extra at https://youtu.be/RzaOPqOpMoM illustrates BlockPy features discussed in the article.